Scheme of Cost Reduction - Planning Commission, Government of India (Planning Commission, Government of India, 1961)
The Cost Reduction Scheme (1961), initiated by the Committee on Plan Projects, outlines strategies to minimize costs in developmental planning, particularly for underdeveloped nations. The scheme emphasizes efficiency in planning, execution, production, inventory, and personnel management, alongside administrative and procedural reforms. Key measures include detailed project requirement assessments, economic analysis, work-study techniques, optimized inventory via A-B-C Analysis, balanced staffing, and streamlined administrative procedures. By adopting systematic and innovative approaches, the scheme aims to counteract inflation, improve productivity, and ensure efficient utilization of resources, contributing to economically sustainable development.
Committee on Plan Projects New Delhi December 1961
Committee on Plan Projects New Delhi
Keywords: Cost Reduction; Planning Efficiency; Project Management; Production Studies; Inventory Management; Personnel Optimization; Administrative Reforms; Economic Analysis; Work-Study Techniques; Resource Utilization